2012
DOI: 10.5152/eajm.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Pulmonary Hydatid Cysts, Which Perforated to the Pleura

Abstract: Objective: Hydatid cyst disease, endemic in Eastern region of Turkey, is a significant parasitic public health problem. In this study, pleural complications of hydatid cysts were presented in 76 cases. Materials and Methods:In our study, of the 412 pulmonary hydatid cyst cases operated on between 2003 and 2011, 76 cases had ruptured into the pleura for various reasons, and the different clinicoradiological presentations were evaluated retrospectively. The age distribution of the cases was between 7 and 56 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
2
15
1
2
Order By: Relevance
“…They suggested that the decision of lobectomy could be made easily by detecting the opening of the lobe bronchus to the cyst cavity with preoperative flexible bronchoscopy. Cangir et al 16) reported bronchial and pleural perforation rates as 21.1% and 3.6%, respectively. In our study, 37.5% (n = 12) of 32 giant cysts were perforated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They suggested that the decision of lobectomy could be made easily by detecting the opening of the lobe bronchus to the cyst cavity with preoperative flexible bronchoscopy. Cangir et al 16) reported bronchial and pleural perforation rates as 21.1% and 3.6%, respectively. In our study, 37.5% (n = 12) of 32 giant cysts were perforated.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, the perforation rates were stated as 24.7%-61%. 10,[14][15][16] Perforation of the cyst can cause hemoptysis, pneumothorax, hydro pneumothorax, empyema, pleural thickening, secondary pleural hydatid disease, and destruction of parenchyma. [17][18][19][20][21] Therefore, some publications suggest more radical surgical procedures such as decortication, segmentectomy, or lobectomy in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned are the most morbid complication of surgery for HCL, the incidence of which is reported to be around 6 to 9% in complicated cysts. 11 In the pneumonostomy technique, the ectocyst must be sutured to the parietal pleura; and if it is not possible, it is important to ensure a watertight closure of pericyst around the Malecot to avoid pneumothorax in the period that it takes for adhesions and a tract to form. Air leak around an inadequately anchored Malecot catheter caused a pneumothorax in one of our patients whose cyst could not be anchored to the parietal pleura.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms included cough (42 cases, 55.2%), chest pain (39 cases, 51.3%), fatigue (32 cases, 42.1%), and fever (28 cases, 36.8%). 9 As a result of the pulmonary hydatid cyst perforating the pleura, symptoms such as chest pain, coughing, cyanosis, fever, and shortness of breath develop. As a result of the rupture of the cyst, the cyst contents pour into the pleura, and the ruptured germinative membrane collapses.…”
Section: Discussionmentioning
confidence: 99%